DOI: 10.11606/t.60.2007.tde-02102008-165058
|View full text |Cite
|
Sign up to set email alerts
|

Emprego de técnicas hifenadas na identificação de metabólitos secundários de 'Lychnophora ericoides' Mart. (Asteraceae) e determinação de suas variações populacionais e temporais

Abstract: GOBBO-NETO, L. Use of hyphenated techniques on the identification of secondary metabolites from Lychnophora ericoides Mart. (Asteraceae) and determination of their populational and temporal variations. 254 f. Thesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 171 publications
(313 reference statements)
0
3
0
2
Order By: Relevance
“…In a previous study conducted by our research group, Gobbo-Neto verified no significant variation between branches collected from the same plant [18]. Therefore, only one branch was collected from each individual plant at mid-height, and all the leaves of this branch were separated and ground.…”
Section: Methodsmentioning
confidence: 94%
“…In a previous study conducted by our research group, Gobbo-Neto verified no significant variation between branches collected from the same plant [18]. Therefore, only one branch was collected from each individual plant at mid-height, and all the leaves of this branch were separated and ground.…”
Section: Methodsmentioning
confidence: 94%
“…The highest concentrations of flavonoids are found in the early evening (9 pm) during the summer (rain season), and caffeoylquinic acids in the afternoon (12 pm to 6 pm ) during the winter (dry season and mild temperatures). [17] In another study, iridoid content in Antirrhinum majus also varies during the day. Although the variation is substantial, no pattern was observed.…”
Section: Circadian Rhythmmentioning
confidence: 93%
“…This reduction was more intense for chlorogenic acids and flavonoids. [17] The seasonal study carried out with the Daucus carota species also identified that flavonoid concentrations are higher in the tissues of new leaves or new spring foliage. [27] In the leaves of Plantago lanceolata L. (Plantaginaceae), the older plants showed concentrations of aucubin, catapol, total iridoid glycosides, and nitrogen approximately one-half that of plants harvested 6 weeks earlier.…”
Section: Seasonal Variationmentioning
confidence: 97%
“…Atualmente, com os avanços da ciência principalmente nas técnicas cromatográficas e de elucidação estrutural, a fitoquímica também determina a influência de variações sazonais, circadianas e populacionais nesta constituição química (GOBBO-NETO, 2007).…”
Section: -Considerações Geraisunclassified
“…Tabela 30 -Dados da análise em CLAE-DAD-EM/EM (modo negativo) em coluna monolítica C-18, do extrato metanólico bruto de M. camporum. (CLIFFORD, 2003(CLIFFORD, , 2005(CLIFFORD, e 2006GOBBO-NETO, 2007), propõe-se que os picos 1, 2 e 4 correspondam respectivamente aos ácidos clorogênicos 5-O-E-cafeoil quínico, 3,5-di-O-E-cafeoil quínico e 4,5-di-O-E-cafeoil quínico.…”
Section: Constituinte Majoritáriounclassified